Prevalence, Clinical and Demographic Characteristics of Helicobacter pylori in Patients Undergoing Esophagogastroduodenoscopy in Specialized Health Centers in Two Departments of the Colombian Coffee Growing Axis - Mejía Valencia, Tatiana (2023)
Helicobacter pylori is a Gram-negative, microaerophilic bacterium with the ability to survive in extreme acid environments, with pH below 4.0. It is estimated that more than half of the world’s population is infected with this bacterium. Objective: To determine the prevalence, clinical and demographic characteristics of Helicobacter pylori infection in patients undergoing esophagogastroduodenoscopy in two specialized centers of the Coffee Growing Axis in Pereira and Manizales from February to October 2018. Method: Cross-sectional descriptive observational study in which the proportion of positivity to Helicobacter pylori in a period of time was determined. Results: The study included 94 patients; the prevalence of positivity to Helicobacter pylori was 86.1% (81/94), 56 (59.5%) of which were diagnosed by culture and 52 (55.3%) by histology. In the histological study, of the 24 (25.5%) subjects who presented precursor lesions of malignancy, 9 (9.5%) were positive for Helicobacter pylori, while in the 70 subjects (74.5%) without precursor lesions of malignancy, 43 (45.7%) were positive. The significant variables for Helicobacter pylori infection were: Histological response for precursor lesions of malignancy: OR of 0.3808 (95% CI: 0.1408-0.9907) p=0.04 and epigastric pain: OR 0.09489 (95% CI: 0.01928-0.3637) p=0.001. Conclusion: The frequency of Helicobacter pylori infection in the Departments of Risaralda and Caldas is high, and does not discriminate against gender, age, race or origin of the study subjects; Epigastric pain continues to be the most relevant symptom in the diagnosis of Helicobacter pylori infection and the combination of diagnostic tests improves the diagnosis of Helicobacter pylori infection.